Implementasi Konsep Green Mining PT. Semen Tonasa: Dampak Lingkungan, Reklamasi, dan Kesejahteraan Petani - Muhammad Fahrullah; Mukhtar Hamzah; Rasdi Rasdi (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This study analyzes the implementation of the Green Mining concept by PT Semen Tonasa and its relationship with environmental sustainability, agricultural productivity, and the welfare of farmers around the mining area. The approach used is descriptive qualitative supported by simple quantitative analysis (Spearman correlation) to assess the relationship between Green Mining metrics (ISO 50001, TSR biomass, land reclamation, and CSR) and community socio-economic indicators. Data were obtained through farmer surveys, interviews with the company and local government, and a review of CSR and energy efficiency documents. The results show that land reclamation exceeded the target of 17.16 ha from 15.85 ha (91.67% success), the implementation of ISO 50001 increased energy efficiency by 18.52%, saved 1,214,159 MWh, and reduced emissions by 435,864 tons of CO₂-e. Biomass substitution increased by 1.17% to 8.13%, followed by a 22.6% increase in rice productivity and a 20% increase in farmer income (Rp 2.5–3.0 million/month). These results confirm Green Mining's significant contribution to energy and economic sustainability, but the unequal distribution of benefits requires tripartite collaboration and the application of the Just Transition principle within the Triple Bottom Line framework.